Evaluation Of The Nutrition Intervention Program In Overcoming Stunting In Toddlers In The Area Of The Astambul Public Health Center, Banjar District, South Kalimantan - fauziah, erna fauziah; Mariana, Evi Risa; Pratiwi, Niken; Hutagaol, Rutmauli (JURNAL CITRA KEPERAWATAN, 2025)
Nutritional issues in toddlers remain a public health challenge, impacting their growth, development, and immune system. Nutrition intervention programs through supplementary feeding (PMT) and growth monitoring have been implemented at the community health center (Puskesmas) and integrated health service posts (Posyandu). However, program effectiveness is largely determined by community acceptance, regular distribution, and the quality of health services. This study aims to evaluate the implementation of the nutrition intervention program for toddlers, including community knowledge, acceptance of assistance, perceived impacts, implementation challenges, and service quality. The study used a quantitative and qualitative approach (mixed methods) using questionnaires and in-depth interviews with mothers of toddlers receiving nutrition assistance. Data were analyzed thematically according to the categories of knowledge, acceptance, impacts, challenges, service quality, and community expectations. The results showed that the majority of respondents were aware of the nutrition intervention program and had received PMT assistance since 2024–2025. The program was assessed as having a positive impact in the form of weight gain, improved appetite, and decreased frequency of illness in toddlers. The quality of services provided by the community health center and integrated health service posts (Posyandu) was appreciated for being friendly and informative. Challenges emerged relatively minor, primarily related to the technical aspects of PMT distribution. Respondents hoped the program would continue with additional nutritious food variations. The nutrition intervention program has proven well-received by the community and has had a positive impact on toddler health. The program's success can be strengthened through diversification of support, ongoing monitoring, and increased participation of integrated health post (Posyandu) cadres in family support. Keywords:Nutrition intervention, toddlers, PMT, integrated health posts, public health